A Study to Assess the Knowledge, Attitude and Practice about Management of Acute Exacerbation of Chronic Obstructive Pulmonary Disease amongst EMS Professionals in Pune, India - Parag Rishipathak1, Anand Hinduja2, Shrimathy V.3, Navnita Sengupta4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Chronic Obstructive Pulmonary Disease (COPD) is one of the common, slow progressivedisorder the respiratory system, considered an important cause of morbidity and mortality across the globe.Although being a chronic disability, COPD presents with acute exacerbations in the form of breathlessnessand cough. Knowledge regarding about diagnosis of COPD, appropriate titration of Oxygen and effectivemanagement are essential to prevent mortality and morbidity due to COPD.Objective: To assess the Knowledge, Attitude and Practice level about management of Acute Exacerbationof COPD among EMS Professionals.Methodology: The study was conducted amongst 100 Emergency Medical Professionals in Pune, India.A previously tested and validated KAP questionnaire prepared by Sylvia Saade et al2 was utilized for thestudy. The questionnaire was administered through online mode after obtaining informed consent from therespondents.Discussion: The analysis of data shows EMS professionals are aware of the aetiology, pathophysiology andclinical features but require more training in management aspects of COPD. In terms of attitude towardsCOPD, broad agreement was found amongst respondents that COPD patients must quit smoking and passivesmoking contributed to COPD. However, opinion amongst respondents with respect to recommendationsregarding exercise was divided. In terms of Practices in COPD, broad consensus was found amongst therespondents on the usage and precautions regarding metered dose inhalers (MDI).Conclusion: The study finding point towards a healthy degree of knowledge, attitude, and practice withregards to COPD amongst EMS professionals. Although the finding do red flag areas of improvement whichcan be focused upon in future training session. The study is limited by number of respondents yet attemptsto provide a broad view on Knowledge, attitude and Practices in COPD.